Analisis Kandungan Zat Gizi Makro dan Daya Terima Bakso Ikan Kembung Substitusi Tepung Kacang Hijau dengan Penambahan Wortel dan Bayam - Rahayu Wiji Astuti; Sukmawati Sukmawati; Hikmawati Mas'ud (INSOLOGI: Jurnal Sains dan Teknologi, 2026)
Pregnant women with Chronic Energy Deficiency (CED) continue to be a public health concern in Indonesia. According to the 2023 Indonesian Health Survey (SKI), 16.9% of pregnant women had CED, which raises their risk of anemia, impaired fetal growth, and low birth weight. One strategy to deal with this problem is by creating functional foods based on local ingredients that are nutritious and acceptable. The aim of this investigation was to examine the macronutrient content and acceptability of mackerel fish meatballs substituted with mung bean flour and enriched with carrots and spinach as a healthy substitute food for expectant mothers with CED. This study used a pre-experimen design with a post-test design consisting of three formulations: F1 (80:20), F2 (50:50), and F3 (20:80). Acceptability testing was conducted on 40 semi-trained panelists using a hedonic test on color, aroma, texture, and taste, and examined using the Kruskal–Wallis test. There were no discernible variations in the outcomes (p>0.05), although F3 was the most preferred formulation. Macronutrient analysis showed that the selected formula contained 116.9 kcal of energy, 10.25% protein, 0.18% fat, and 18.57% carbohydrates. This product has the potential as a functional food to support nutritional improvement in pregnant women with CED.